External Electric Field-Dependent Photoinduced Electron Transfer of Oligonaphthofurans-PC70BM in BJH Solar Cell (Journal of Atomic and Molecular Sciences, 2017)
To rely mainly on the impact of external electric field derived from the electronic coupling chargetransfer rate in the change, the new theoretical method can not merely a better understanding of chemicalstructure, the external electric field and optoelectronic properties of donor(D)-acceptor(A) system, but alsocan be used for reasonable design of D-A system of novel organic solar cells. This article selects PC70BM(phenyl-fullerenes-butyric acid methyl ester) (good solubility, high electron mobility, with common polymermaterial to take shape a fine phase separation) as this acceptor; low five different kinds of chain length ofoligonaphthofurans molecules (active material of fluorescent probe molecule) as the donor, using densityfunctional theory on the basis of the Marcus theory to calculate the electronic coupling, reorganizationenergy, gibbs free energy of reaction, rates of the charge recombination and the rates of exciton dissociationfor this study.